Current Patterns of Management of Advanced Prostate Cancer in Routine Clinical Practice in Spain - Maria José Ribal; Juan Ignacio Martínez-Salamanca; Camilo García Freire (Prostate Cancer)
Objective. To describe urologists’ practice patterns when managing patients with advanced prostate cancer (PCa) in Spain. Methods. This was an observational study conducted by 120 urologists using retrospective data of advanced PCa patients attending hospitals and outpatient centers. Results. Urologists evaluated a total of 375 patients (mean age: 75 years; ECOG 0-1: 77%; mean serum PSA levels at study entry: 50.5 ng/Ml). Approximately 50% of patients had bone metastases, and 60.6% experienced pain as the main symptom of progressive disease. Primary androgen deprivation therapy (ADT) use was 99.7%, with continuous ADT as the dominant strategy (91.9%). After failure of initial ADT, antiandrogen withdrawal was the next method most commonly used in 57% of patients. Choice of secondary hormonal treatment was made mostly by urologists (96%), who continued to monitor patients. Patient follow-up after chemotherapy and supportive care were mainly done in urology units, although responsibility was shared with medical oncologists and radiologists. Conclusion. The urologists’ attitudes towards management of PCa in the routine practice in Spain show the urologist as an integral component even when patients progress to advanced stages of the disease.